Aspectos cognitivos e metodológicos na utilização do jogo xeque-mate soccer - Souza, Herycksara Santos de (2013)
The explanation for the large number of papers on game rules in developmental psychology is the diversity of its use. It is possible to use this tool in the context of assessment or intervention, providing characteristics of the subject's cognitive and affective dimensions. This paper proposes the creation of a game that mixes soccer and chess skills, the Checkmate Soccer. Its objective was to verify the functionality of the tool with adolescent participants. Four teenagers average age of 16 years, male and female, participated in the study. Data collection occurred in two phases, one was a championship and another was the meeting to interview and solve the problem situations. Analysis were then performed following the criteria of genetic psychology and genetic epistemology, based on the theory of Jean Piaget. The results indicate that the Checkmate Soccer game is an effective instrument considering the objectives proposed in this work, and given that it was possible to analyze the performance of the participants through the matches, using the heuristic parameter levels developed for this. Therefore, the instrument Checkmate Soccer game of rules, was considered an efficient working tool, because it is able to provide analyzes of cognitive elements in a playful way.